Growth Kinetics of Monodisperse Polystyrene Microspheres Prepared by Dispersion Polymerization. (5th June 2013) - Li, Fan; Geng, Chong; Yan, Qingfeng
Abstract : Dispersion polymerization has been widely applied to the synthesis of monodisperse micron-sized polymer colloidal spheres. Many efforts have been devoted to studying the influence of initial conditions on the size and uniformity of the resultant microspheres, aiming to synthesize micron-size monodisperse colloidal spheres. However, the inner contradiction between the size and the size distribution of colloidal spheres hinders the realization of this goal. In this work, we drew our attention from the initial conditions to the growth stage of dispersion polymerization. We tracked the size evolution of colloidal sphere during the dispersion polymerization, through which we established a kinetic model that described the relationship between the monomer concentration and the reaction time. The model may provide a guideline to prepare large polymer colloidal spheres with good monodispersity by continuous monomer feeding during the growth stage to maintain the concentration of monomer at a constant value in a dispersion polymerization process.